Analisis Semantik Kata Shirath Dalam Al-Qur’an - Gunarti, Tri Tami; Mubarok Ahmadi; Pratiwi, Intan (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
In the Quran, there are numerous terms that use the word "shirath" in its singular form or in conjunction with other words. The word "shirath" is often translated as a narrow bridge to heaven or a bridge as thin as a hair. This study aims to explore the meaning of "shirath" as found in the Quran and to examine its implications in social life. The word "shirath" is mentioned 43 times in the Quran with various derivations, making it an interesting subject for research. The method used is qualitative with a library research approach, utilizing primary data from Quranic exegesis and Hadith, as well as secondary data from journals, scholarly articles, and references related to the research. The analysis employed in this study is based on the semantics of Toshihiko Izutsu. The results indicate that "shirath" represents the straight path to heaven. In social life, "shirath" is interpreted as following Allah's commands and avoiding His prohibitions.